PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 4 PARIAMAN - Wulandari, Novi; Asri, Yasnur; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This article was written to illustrate the effect of using problem based learning model with serialized media relation to writing skill of exposition of VIII students of SMP Negeri 4 Pariaman. This research data is a score in the skills of writing exposition texts before and after using the problem-based model of learning assisted media series image. This study has three results. First, the skills of writing expository texts before using the problem based learning model with the help of the medium of serial images are in the qualification Enough (C). Second, the skill of writing the text of the exposition of the students of grade VIII SMP Negeri 4 Pariaman after using the problem based learning model assisted by the media of the series is qualified More than Enough (Ldc). Third, based on the t test concluded that there is a significant influence on the skill of writing expository text because thitung> ttabel (5,54> 1.70).Kata kunci: pengaruh, model problem based learning, media gambar berseri, menulis teks eksposisi